ENT 530 Social Media Portfolio: Uncle Bob By Aizat / Muhamad Aizat Afiq Che Nordin - Che Nordin, Muhamad Aizat Afiq (2021)
Uncle Bob by Aizat offers fried food that is made from high quality premium ingredients special for all fried food lovers. We are selling three products which are Ayam Gunting, Sotong Gunting and Sosej Cheese Jumbo that is very juicy and delicious. We are also selling our product at a reasonable and affordable price so that everyone will be able to try our product. Uncle Bob by Aizat clients are the customers that love to eat fried food while watching movies at anytime and anywhere when they feel like to munch something. Uncle Bob by Aizat are also targeting students that seek for something to eat while they are studying because this food can help them to reduce their boredness and stress level while doing assignments. Our business has started around the middle of 2021. We provided a services direct delivery to customers or self pickup for customer around Shah Alam, Selangor. We believe that our product is a good marketable product of choice that can be further expanded to many different areas as the business keep growing. We have a Facebook page to expand our business through social media and learn how to post Facebook posts for business products which consists of teaser post, soft sell and hard sell.